2020
DOI: 10.30976/susead.705821
|View full text |Cite
|
Sign up to set email alerts
|

Örgüt Kültürü Algisinin Örgütsel Çevi̇kli̇k Üzeri̇ndeki̇ Etki̇si̇ni̇n İncelenmesi̇

Abstract: Bu çalışmanın amacı, çalışanların örgüt kültürü algılarının örgütsel çeviklik üzerindeki etkisini incelemektir. Çalışma kapsamında öncelikle örgüt kültürü ve örgütsel çeviklik hakkında kavramsal çerçeve oluşturulmuş, ardından araştırma kapsamında gerçekleştirilen anket uygulamasından elde edilen bulgu ve sonuçlara yer verilmiştir. Araştırma örneklemi, Kırşehir ilinde faaliyet gösteren ve çalışan sayısı 100-250 arasında bulunan özel sektör kuruluşlarının 415 çalışanından oluşmaktadır. Araştırmada nicel veri ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Aktemur (2016) focused on the relationship between organizational culture and many leadership styles and concluded that organizational culture was related to leadership. Basri and Zorlu (2020) touched upon the effect of perceived organizational culture on organizational agility and concluded that perceived organizational culture was related to organizational culture. Yet another study examining the relationship between agile leadership and organizational culture was conducted by Kompella (2014), who concluded that there was a relationship between agile leadership and organizational culture.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Aktemur (2016) focused on the relationship between organizational culture and many leadership styles and concluded that organizational culture was related to leadership. Basri and Zorlu (2020) touched upon the effect of perceived organizational culture on organizational agility and concluded that perceived organizational culture was related to organizational culture. Yet another study examining the relationship between agile leadership and organizational culture was conducted by Kompella (2014), who concluded that there was a relationship between agile leadership and organizational culture.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Nafei (2016) found that all items yielded alpha scores higher than 0.70 and the overall reliability of the scale was calculated as 0.8914. Also, Basri and Zorlu (2020) have adopted this scale in their study regarding the impact of organizational culture on organizational agility and found out that the scale was reliable and valid. 5-point Likert scale was used to rate all questionnaire questions (strongly disagree: 1, disagree: 2, neither agree nor disagree: 3, agree: 4, fully agree: 5) and IBM SPSS statistics program was used to analyse the survey data.…”
Section: Methodsmentioning
confidence: 99%
“…Çıkabilecek sorunlara müdahale ve hızlı çözüm üretme yeteneği olarak işletmenin örgütsel çeviklik düzeyinin yüksek tutulması gerektiği ifade edilebilir (Pelit, 2008: 9). Konuyla ilgili olarak Basrı & Zorlu (2020), 100 ile 250 kişi arasında çalışanı olan ve Kırşehir ilinde faaliyet gösteren özel sektör işletmeleri üzerinde bir araştırma gerçekleştirmişlerdir. Araştırmada çalışanların örgüt kültürü algılarının örgütsel çeviklik düzeyleri üzerindeki etkisinin hangi seviyede olduğunu ölçmeyi hedeflemişlerdir.…”
Section: öRgütsel Dna Ve öRgütsel çEviklik Arasındaki İlişkiunclassified